Validation of the multiresidual GC-MS method for determining plant protection product residues in strawberries - Helena BAŠA ČESNIK (Acta Agriculturae Slovenica)
Gas chromatography coupled with mass spectrometry was used for the introduction and validation of the multiresidual method for determining of plant protection product residues in strawberries. During the validation procedure, limits of quantification were set and the method was checked for its recovery, linearity, repeatability, reproducibility and measurement uncertainty. An interlaboratory comparison was also performed to check the accuracy of the method. The method was proven to be fit for purpose. Afterwards 19 strawberry samples were analysed for the presence of plant protection product residues using the validated method. In the strawberries 5 active substances, all fungicides, were found: chlorothalonil, cyprodinil, fludioxonil, metalaxyl+metalaxyl-M and pyrimethanil. Residues of these active substances were in range 0.01 – 0.44 mg/kg. No cases exceeding the maximum residue levels were measured.